Digital Religion: Content Analysis of Female Religious Influencers on Instagram in Kazakhstan - Abdilkhakim, B. (Eurasian Journal of Religious Studies, 2025)
Social media platforms have become significant tools for religious communication and propaganda, and in this context, the role of female influencers has been increasingly prominent. This study examines the content creation practices of prominent female religious influencers on Instagram, focusing on their strategies, themes, and audience engagement. By analyzing selected case studies, the research explores how these influencers intertwine economic, religious, and psychological themes in their content. Particular attention is given to the use of personal experiences, the integration of patriarchal traditions, and religious-philosophical elements as part of their narratives. The study also investigates the monetization strategies employed by these bloggers, including book publications, online courses, social media branding, and event organization such as marathons. The findings highlight how these influencers cater to the spiritual and material needs of their audiences while building personal brands and public images through social media platforms. Furthermore, the study contextualizes these practices within broader trends in Kazakh society. The article reveals new trends in the Kazakh media landscape by highlighting the unique approaches of female bloggers in creating and promoting content on social media compared to traditional religious institutions and their representatives.Keywords: Religious Influencer, Islam, Social Media, Instagram, Blogging